Breast cancer among Yemeni women using the National Oncology Centre Registry 2004-2010 - Zaemey, S.; Nagi, N.; Fritschi, Lin; Heyworth, J. (Elsevier Inc., 2012)
Background: In developing countries including Arab countries breast cancer is one of the most common cancers found in women. Even though breast cancer incidence is lower in Arab developing countries than in western countries, Arabic women are more likely to be diagnosed at an earlier age than the women in western countries. Method: A descriptive study was undertaken to investigate the type of breast cancer, lymph node involvement, side of breast and, region and age distribution of breast cancer patients registered in the National Oncology Centre in Yemen. Results: From September 2004 to December 2010, 2654 women across Yemen diagnosed with breast cancer were registered in the National Oncology Centre for treatment. Between the years 2004 and 2010, breast cancer represented 22% of all cancers registered in women. Seventy-one per cent of the women were aged 50 or younger at the time of diagnosis. The most common age group affected was women aged 41–50 years, with (35%) of cases occurring in this age. Invasive ductal carcinoma was the most common pathology (76%) and 79% of the patients had lymph node involvement at the time of diagnosis. Approximately 2% had bilateral disease and the frequency of left (44%) and right breast cancer (42%) were similar. Conclusion: This study has shown that breast cancer is a disease of young women in Yemen. The majority of women presented with lymph node involvement. Hence efforts are needed to increase breast cancer awareness in Yemen for early detection at all age groups, and to target women living in areas that have lower access to health care services.